Effect of eCG in a short-term synchronization treatment on ovarian status, estrus synchrony, and ovulation in dairy goats managed under tropical conditions - Pereira de Andrade, Amanda Bricio; Cruz Morais, Maria Clara; Cerqueira Rangel, Paulo Sergio; Franco Oliveira, Maria Emilia [UNESP]; Goncalves Souza-Fabjan, Joanna Maria; Fonseca, Jeferson Ferreira (Springer, 2021)
The aim of this study was to assess the need of using eCG on short-term estrus synchronization protocol in nulliparous (NUL) and multiparous (MULT) dairy goats during the breeding season. Alpine (n = 20), Nubian (n = 20), and Saanen (n = 16) goats received 60 mg medroxyprogesterone acetate intravaginal sponges for 6 days plus 30 mu g d-cloprostenol and 200 IU eCG (G-eCG, n = 28) or saline (G-Control, n = 28) 24 h before sponge removal. The NUL and MULT goats of each breed were equally assigned into the two treatments. Transrectal ultrasonography was used to evaluate ovulatory parameters, and teaser goats were used for estrus detection every 12 h from sponge removal to ovulation. eCG did not affect (P > 0.05) estrus response (similar to 86%), diameter of ovulatory follicles (similar to 6.8 mm), and number of ovulations (similar to 1.6). Nevertheless, eCG led to earlier (P < 0.05) ovulation (G-eCG = 65.1 and G-Control = 73.2 h) and increased (P < 0.05) the ovulation rate (G-eCG = 96.4% and G-Control = 67.9%). In the absence of eCG, no differences regarding reproductive parameters (P > 0.05) were found between parity orders. Alpine MULT goats underwent a superior (P < 0.05) number of ovulations (2.2) in comparison to NUL goats (1.3). In conclusion, the exclusion of eCG from short-term estrus synchronization protocol did not interfere with estrus response but decreased the ovulation rate.
Keywords: Reproduction; Hormone; Does; Nulliparous; Multiparous; Gonadotropin